SET1/MLL family of proteins: functions beyond histone methylation - Jeyapal Sugeedha; Jyoti Gautam; Shweta Tyagi (Epigenetics, 2021)
The SET1 family of enzymes are well known for their involvement in the histone 3 lysine 4 (H3K4) methylation, a conserved trait of euchromatin associated with transcriptional activation. These methyltransferases are distinct, and involved in various biological functions in the cell. Impairment in the function of SET1 family members leads to a number of abnormalities such as skeletal and neurological defects, leukaemogenesis and even lethality. Tremendous progress has been made in understanding the unique biological roles and the mechanism of SET1 enzymes in context with H3K4 methylation/canonical functions. However, in recent years, several studies have indicated the novel role of SET1 family proteins, other than H3K4 methylation, which are equally important for cellular functions. In this review, we focus on these non-canonical function of SET1 family members.